The Effect of Customer Reviews on Impulsive Buying at Tik Tok Stores (Study Generation Z in Indonesia) - Irwan Christanto; Setyani Sri Haryanti (Indonesian Journal of Business Analytics, 2024)
The purpose of this study is to ascertain how online customer reviews, which are influenced by price consciousness, risk perception, and trust, affect impulsive online purchases on Tik Tok. Generation Z is the group of people who have made purchases on Tik Tok and are now patrons of the Tik Tok online store. Purposive random sampling was the approach used for sampling. First, they must be members of Generation Z; second, they must have made a purchase on TiK Tok. A sample of 135 members of the Z generation was acquired. Smart-PLS was used to analyze the data. The study's findings indicate that: 1) customer reviews have a favorable impact on impulsive online purchases made on Tik Tok; and 2) customer reviews have a negative impact 3) risk perception positively impacts impulsive buying; 3) risk perception positively impacts trust; 4) customer reviews positively impacts trust; 5) trust positively impacts impulsive buying; and 6) customer reviews positively impacts impulsive buying decisions made online. The relationship between customer reviews and impulsive buying is moderated by price consciousness.